Discourse analysis on the use of language by fundamentalist and moderate Islamic groups on Facebook - Wildan, M; Ridwan, Muhammad (Diksi, 2025)
This study explains the discourse on language use that occurs in fundamental and moderate Islamic groups on Facebook. The design of this study utilized a qualitative descriptive method. The data were in the forms of Facebook statuses uploaded by fundamental and moderate Islamic groups. The data sources were from 20 Facebook accounts affiliated with fundamental and moderate Islam. The data collection technique was carried out by observing Facebook status and layer captures. Data analysis was carried out through several stages by way of categorizing data and applying narrative analysis techniques. A data triangulation technique was carried out to check data validity. The results of this study show fundamental Islamism as a form of language identity expression and language identity among moderate Muslims. This finding has implications that language is not just a medium for conveying information to opponents, but also a battle of Islamic ideologies that fundamentalists and moderate Islamists uphold.